Combination Targeting of Subthalamic Nucleus and Ventral Intermediate Thalamic Nucleus in Deep Brain Stimulation for Tremor-Dominant Parkinson's Disease: Experience and Outcomes. (1st September 2019) - Fayed, Islam; Cobourn, Kelsey Diva; Pivazyan, Gnel; Pagan, Fernando; Lo, Steven; Torres-Yaghi, Yasar; Mandir, Allen S; Kalhorn, Christopher G
Abstract: INTRODUCTION: Deep brain stimulation (DBS) has traditionally been used to target the subthalamic nucleus (STN) or globus pallidus internus (GPi) to treat the bradykinesia and rigidity of Parkinson's disease (PD) and the ventral intermediate thalamic nucleus (VIM) to treat essential tremor (ET). Recent case reports have described targeting both the STN and VIM with a single trajectory to treat patients with tremor-dominant PD; yet, outcome data for this procedure remain sparse. METHODS: We conducted a single-center retrospective review of all patients who underwent combined STN-VIM DBS. Demographic and outcome data, including Unified Parkinson Disease Rating Scale (UPDRS), changes in symptom severity, and levodopa equivalent daily dose (LEDD), were collected and analyzed. RESULTS: Nineteen patients underwent combined STN-VIM trajectory DBS between January 2013 and April 2019. Patients were 90% male and 10% female, with an average age of 63.6 ± 12 yr. Average preoperative UPDRS was 24.2 and LEDD was 807.8. At an average follow-up of 23.9 mo, UPDRS and LEDD decreased by an average of 9.25 and 404.8, respectively. A total of 95% of our patients reported an improvement in tremor symptoms, and 58% were able to decrease the total medication burden. CONCLUSION: Combined targeting of STN and VIM thalamus for tremor-dominant PD results in an excellent control of tremor symptoms, as well as a decrease in UPDRS and LEDD. Larger multicenter studies are necessary to validate this as the optimal DBS target for tremor-dominant PD.